Worry about professional education: Emotions and affect in the context of neoliberal change in postsecondary education. (February 2018) - Moffatt, Ken; Todd, Sarah; Barnoff, Lisa; Pyne, Jake; Panitch, Melanie; Parada, Henry; McLeod, Sandy; Hunter Young, Nataleah
Highlights: The emotional/affective landscape of professors within the neoliberal university. Development of worry as both an affect and an emotion. The bind of professional schools in the context of neoliberal change. Resistance to decontextualized understanding of caring.